(3eTGQY GdCThGb Edi eUGQY GdYTGb heKjQ GdZQGe Edi OGQ GdSdGes - (3eMji GdOjf CMeO Hf EHQGgje Hf eMeO Hf GdfMGS GdOeTbjs; (3CHhYHO Gddg HgGA GdOjf eMeO Hf EHQGgje Hf eMeO Hf GdfMGS GdMdHj,J (B698 (3g` s ((3CMeO Hf YHOGdQMje GdYQGbj s)
(3ChdgG (B:s
(3CeG HYO aef GdeYdhe Cf GdNdb cdge edc ddg hYHjO hGf Gddg jaYd aj edcg hedcg eG ojQjO s
(3BNQgG (B:s
(3hHYV CdaGXg UQjM hGddg CYde s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B297s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1686s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs